Uncanny valley: A preliminary study on the acceptance of Malaysian urban and rural population toward different types of robotic faces - Tay T.T.; Low R.; Loke H.J.; Chua Y.L.; Goh Y.H. (Institute of Physics Publishing, 2023)
Animals; Anthropomorphic robots; Integrated circuits; Robotics; Stars; Surveys; Cartoon characters; Cultural backgrounds; European Countries; Interactive robotics; Preferred features; Questionnaire surveys; Robotic technologies; Robotics technology; Landforms